Deep learning‐based forward and cross‐scatter correction in dual‐source CT. Issue 9 (13th August 2021) - Erath, Julien; Vöth, Tim; Maier, Joscha; Fournié, Eric; Petersilka, Martin; Stierstorfer, Karl; Kachelrieß, Marc
Abstract: Purpose: Dual‐source computed tomography (DSCT) uses two source‐detector pairs offset by about 90°. In addition to the well‐known forward scatter, a special issue in DSCT is cross‐scattered radiation from X‐ray tube A detected in the detector of system B and vice versa. This effect can lead to artifacts and reduction of the contrast‐to‐noise ratio of the images. The purpose of this work is to present and evaluate different deep learning‐based methods for scatter correction in DSCT. Methods: We present different neural network‐based methods for forward and cross‐scatter correction in DSCT. These deep scatter estimation (DSE) methods mainly differ in the input and output information that is provided for training and inference and in whether they operate on two‐dimensional (2D) or on three‐dimensional (3D) data. The networks are trained and validated with scatter distributions obtained by our in‐house Monte Carlo simulation. The simulated geometry is adapted to a realistic clinical setup. Results: All DSE approaches reduce scatter‐induced artifacts and lead to superior results than the measurement‐based scatter correction. Forward scatter, under the presence of cross‐scatter, is best estimated either by our network that uses the current projection and a couple of neighboring views (fDSE 2D few views) or by our 3D network that processes all projections simultaneously (fDSE 3D). Cross‐scatter, under the presence of forward scatter, is best estimated using xSSE XDSE 2D, with xSSE referring to a quick single scatter estimate of cross scatter, or by xDSE 3D that uses all projections simultaneously. By using our proposed networks, the total scatter error in dual could be reduced from about 18 HU to approximately 3 HU. Conclusions: Deep learning‐based scatter correction can reduce scatter artifacts in DSCT. To achieve more accurate cross‐scatter estimations, the use of a cross‐scatter approximation improves the results. Also, the ability to leverage across different projection angles improves the precision of the algorithm. Abstract :